2007
DOI: 10.1097/01.brs.0000257341.88880.f1
|View full text |Cite
|
Sign up to set email alerts
|

Fibroblast Growth Factor-2 Maintains the Differentiation Potential of Nucleus Pulposus Cells In Vitro

Abstract: The presence of FGF-2 during culture expansion of nucleus pulposus cells in monolayer can sustain a differentiated cell phenotype by maintaining responsiveness to TGF-beta1. Our results suggest that FGF-2 should be tested for its ability to maintain the reactivity of the nucleus pulposus cells to other morphogenic factors that may be used for cell-based transplantation therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
47
0
2

Year Published

2008
2008
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(53 citation statements)
references
References 43 publications
4
47
0
2
Order By: Relevance
“…In the bovine IVD, we have found that bFGF released by chondrocytes after mechanical injury favors catabolism by stimulating MMP-13 production, inhibiting PG synthesis, and antagonizing the well-known cartilage anabolic activity of BMP7 (Li et al, 2008). Interestingly, Li et al (2008) found that bFGF stimulates an overall increase in sulfated PG synthesis in bovine NP tissue, similar to results reported by Tsai et al (2007). However, after normalization to cell number, both DMMB and 35 S-sulfate incorporation results suggested that, per cell, total PG accumulation and PG synthesis significantly decreased with bFGF stimulation in a dose-dependent manner (Li et al, 2008), suggesting a negative regulatory function of bFGF in spine cartilage homeostasis.…”
Section: (B) Actions Of Bfgf In the Ivdsupporting
confidence: 79%
See 3 more Smart Citations
“…In the bovine IVD, we have found that bFGF released by chondrocytes after mechanical injury favors catabolism by stimulating MMP-13 production, inhibiting PG synthesis, and antagonizing the well-known cartilage anabolic activity of BMP7 (Li et al, 2008). Interestingly, Li et al (2008) found that bFGF stimulates an overall increase in sulfated PG synthesis in bovine NP tissue, similar to results reported by Tsai et al (2007). However, after normalization to cell number, both DMMB and 35 S-sulfate incorporation results suggested that, per cell, total PG accumulation and PG synthesis significantly decreased with bFGF stimulation in a dose-dependent manner (Li et al, 2008), suggesting a negative regulatory function of bFGF in spine cartilage homeostasis.…”
Section: (B) Actions Of Bfgf In the Ivdsupporting
confidence: 79%
“…However, after normalization to cell number, both DMMB and 35 S-sulfate incorporation results suggested that, per cell, total PG accumulation and PG synthesis significantly decreased with bFGF stimulation in a dose-dependent manner (Li et al, 2008), suggesting a negative regulatory function of bFGF in spine cartilage homeostasis. In addition, while we (Li et al, 2008) and others (Tsai et al, 2007) have found that bFGF stimulates both collagen type I and II gene expression in the IVD, the ratio of collagen II:collagen I is significantly decreased in bovine IVD tissue (Li et al, 2008), presumably via increased collagen type I synthesis by fibrocytelike cells leading to the formation of fibrocartilage.…”
Section: (B) Actions Of Bfgf In the Ivdmentioning
confidence: 63%
See 2 more Smart Citations
“…2g-i). FGF-2 sustains the differentiated phenotype of cultured NP cells by maintaining their responsiveness to TGF-b [140]. FGF-2 also increases the numbers of inflammatory cells, including macrophages, lymphocytes, and fibroblasts in herniated disc and facilitates the resorption of material extruded into the epidural space [86].…”
Section: Rim Lesions and The Etiopathogenesis Of Disc Degeneration Inmentioning
confidence: 99%